The Journey of American Capitalism: From Stockholders to Stakeholders - Reavis, Mark Ray; Orr, David W. (American Journal of Management, 2021)
The American practice of capitalism has been nothing short of dynamic. The struggle to find an acceptable method of ‘the proper administration of wealth’ has been a key issue since at least the days of Andrew Carnegie. In the early years of American industrialization, the focus was largely and legally on stockholder rights. This focus shifted somewhat towards the benefit of labor as unions gained power in the early 20th century. Then, the stakeholder view began to take root and grow in the last half of the 20th century. This view expanded the conversation of capitalists vs. labor to include other stakeholders. This research reviews history and literature on the journey of American capitalism and takes the additional step of addressing expectations of corporate governance changes in the near future and the impact millennials are likely to have on the journey.